Development of a Spatial Decision Support System for Land Use Planning - Aljack, Elsadig Abdalla (2001)
Land use planning and management have an obvious spatial dimension where complex models and methods of assessment are used. The use of information technologies and spatial concepts promise many benefits to planners and decision-makers in the land use planning process. However, current land use planning systems lack flexibility in accommodating changes of land use parameters. This prevents decision makers from generating alternate land use scenarios. This research aims to develop a flexible Spatial Decision Support System for Land use Planning (SDSS-LP). The SDSS-LP development lifecyc1e methodology consists of five phases, namely, planning, analysis, design, implementation and testing phases. SDSS-LP was developed in the modules by using Arc View programming language A venue and dialog designer extension. The system modules are categorized into three subsystems i.e. database management, analysis and modeling. The system permits decision-makers to view and access its own planning domain database without any constraints. Next, SDSS-LP also helps the decision-makers to manipulate and analyze spatial and attribute data so as to be able to decide on significant suitability factors. These factors will facilitate the production of alternative allocation maps that can be used to represent different planning scenario. Thus, the SDSS-LP is valuable software that can be used within the land use planning process.